Investigation of physical parameters influencing body awareness in adults with obesity: An observational, controlled study - ERSÖZ HÜSEYİNSİNOĞLU, BURCU (My University, 2024)
Aim: The primary aim was to compare the body awareness (BA) level in adults with obesity and non-obese adults. The secondary aim was to investigate the physical parameters associated with BA and compare them between adults with obesity and non-obese adults. Method: Thirty-two adults with obesity and age and sex-matched 32 non-obese adults were included in the study. The outcome measures were the Body Awareness Questionnaire, International Physical Activity Questionnaire-Short Form and Functional Reach Test to detect BA, physical activity (PA), and dynamic balance level, respectively. Reaction time was assessed by the Nelson Foot Reaction Test and knee and trunk position error by inclinometer. Results: There was no significant difference between the obese and non-obese group in terms of BA score (p = 0.18) and PA level (p = 0.50). Lower dynamic balance was observed in the obese group (p = 0.003). Only the trunk position error was higher in the obese group in the measurement of joint position error (p = 0.010). There were no significant differences in the right and left feet reaction times between the groups (p = 0.68 and p = 0.23). There were no relationships between BA score and PA level (p = 0.93), dynamic balance (p = 0.82), joint position error (p = 0.14), and right (p = 0.33) and left (p = 0.25) reaction times. Conclusion: There was no significant difference in body awareness between the non-obese and the obese group and there was no association between body awareness and the physical parameters. However, adults with obesity had impaired balance and proprioception compared to non-obese ones.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; ENTEGRE VE TAMAMLAYICI TIP; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; INTEGRATIVE & COMPLEMENTARY MEDICINE; Tamamlayıcı ve Manuel Terapi; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Rehabilitasyon; Tamamlayıcı ve Alternatif Tıp; Complementary and Manual Therapy; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; Complementary and Alternative Medicine; Balance; Body awareness; Obesity; Physical activity; Proprioception; Reaction